2007
DOI: 10.1093/ejo/cjm039
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness and patient satisfaction: Hawley and vacuum-formed retainers

Abstract: In the United Kingdom (UK) over the last 10 years, there has been a significant increase in the use of vacuum-formed retainers (VFRs) rather than conventional Hawley retainers. There are currently no data to compare the cost-effectiveness of this change in practice. The two aims of this study were to compare (1) the cost-effectiveness of VFRs and Hawley retainers over 6 months, from the perspective of the National Health Service, orthodontic practice, and the patient and (2) patient satisfaction in the two ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
136
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(152 citation statements)
references
References 13 publications
8
136
2
Order By: Relevance
“…Thermoplastic clear retainers have increased in popularity as a result of their esthetic and translucent properties. [2][3][4] Though preferred because of their translucent nature, it has been reported 5 that the physical properties of thermoplastic retainers can be changed as a result of intraoral temperature fluctuations, as well as the retainers being subjected to cyclic deflections. Previous studies have reported poor wear resistance and durability of orthodontic appliances after ''short service periods''; furthermore, similar studies on mouth guards, made from comparable thermoplastic orthodontic materials, have demonstrat-ed various dimensional changes induced by aging, again depending on the particular material and processing techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Thermoplastic clear retainers have increased in popularity as a result of their esthetic and translucent properties. [2][3][4] Though preferred because of their translucent nature, it has been reported 5 that the physical properties of thermoplastic retainers can be changed as a result of intraoral temperature fluctuations, as well as the retainers being subjected to cyclic deflections. Previous studies have reported poor wear resistance and durability of orthodontic appliances after ''short service periods''; furthermore, similar studies on mouth guards, made from comparable thermoplastic orthodontic materials, have demonstrat-ed various dimensional changes induced by aging, again depending on the particular material and processing techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Since being introduced into the UK National Health Service fee structure in 1996, the rate of increase in the use of VFRs has been approximately nine times greater than that of Hawley retainers. 9 A vacuum machine adapts heat-softened plastic by negative pressure, creating a vacuum, and pulls the plastic onto a working study cast. The two most common materials used for VFRs are polyethylene copolymers and polypropylene polymers.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of patients appear to prefer VFRs over Hawley retainers, and VFRs are less likely to be broken. 9,11 However, recent studies have found that there appear to be some problems with the physical properties of VFRs, in particular their resistance to wear. Campbell et al 12 looked into the reasons for replacement of VFRs over a 1-year period.…”
Section: Introductionmentioning
confidence: 99%
“…4,16,17 The purpose of the current study was to discern patients' opinions regarding responsibility for orthodontic retention and to determine associations between patient attitudes toward retention and perceptions of treatment success.…”
Section: Introductionmentioning
confidence: 99%